Adipose Stem Cell-Derived Extracellular Vesicles Induce Proliferation of Schwann Cells via Internalization - Maximilian Haertinger; Tamara Weiss; Anda Mann; Annette Tabi; Victoria Brandel; Christine Radtke (Cells, 2020)
Recent studies showed a beneficial effect of adipose stem cell-derived extracellular vesicles (ADSC-EVs) on sciatic nerve repair, presumably through Schwann cell (SC) modulation. However, it has not yet been elucidated whether ADSC-EVs exert this supportive effect on SCs by extracellular receptor binding, fusion to the SC membrane, or endocytosis mediated internalization. ADSCs, ADSC-EVs, and SCs were isolated from rats and characterized according to associated marker expression and properties. The proliferation rate of SCs in response to ADSC-EVs was determined using a multicolor immunofluorescence staining panel followed by automated image analysis. SCs treated with ADSC-EVs and silica beads were further investigated by 3-D high resolution confocal microscopy and live cell imaging. Our findings demonstrated that ADSC-EVs significantly enhanced the proliferation of SCs in a time- and dose-dependent manner. 3-D image analysis revealed a perinuclear location of ADSC-EVs and their accumulation in vesicular-like structures within the SC cytoplasm. Upon comparing intracellular localization patterns of silica beads and ADSC-EVs in SCs, we found striking resemblance in size and distribution. Live cell imaging visualized that the uptake of ADSC-EVs preferentially took place at the SC processes from which the EVs were transported towards the nucleus. This study provided first evidence for an endocytosis mediated internalization of ADSC-EVs by SCs and underlines the therapeutic potential of ADSC-EVs in future approaches for nerve regeneration.